Analysis of the pre-service primary teacher education curriculum in East Pakistan and recommendations for its improvement - Khatun, Razia Akhtar (Khan) 1937- (s.n.], 1971)
The pre-service primary teacher education curriculum in East Pakistan was analyzed on the following five phases: the general frame and organization, contents, methods and techniques, student teaching practices and co-curricular activities and evaluation procedures in this study. The research method employed was documentary analysis.